The Implementation of Blockchain Technology in the Education Sector - Nur Wahid, Wahyu; setyowati, Widhy; Wahyu Sejati (Blockchain Frontier Technology, 2024)
The development of technology, especially with the introduction of 5G cellular networks, has had a significant impact on ubiquitous computing. In this context, blockchain technology plays a crucial role by providing security assurance to operating systems through distributed ledgers. This research explores the applications of blockchain in education, focusing on solving issues in the teaching learning process, protecting intellectual property rights, certifying course credits, issuing digital certificates, and sharing resources. The research employs data collection methods, and the analysis of blockchain’s advantages and features, as well as its current applications, reveals its benefits in the field of education. The results and discussions reflect the challenges and potential of implementing blockchain technology, emphasizing the need for careful consideration regarding data security. The conclusion states that blockchain can be successfully applied in education, provided it is understood and implemented with precision. This significantly contributes to meeting the needs and demands of contemporary education.